DAMPAK TREN TIKTOK TERHADAP GAYA HIDUP REMAJA DI DESA BANGKO PERMATA KECAMATAN BANGKO PUSAKO ROKAN HILIR - Rahayu Marina Sari; Resdati Resdati (LPPM Institut Pendidikan Nusantara Global, 2023)
This research was conducted in Bangko Permata Village, Bangko Pusako Rokan Hilir District. The purpose of the study was to find out: 1) the Tiktok User Phenomenon for Teenagers and 2) Tiktok Trends towards the Teenager Lifestyle. This study used qualitative research methods by taking 5 research subjects aged 16-19 years. This study used purposive sampling techniques through data collection techniques using observation, interviews, and documentation. The theory used is lifestyle theory according to David Chaney and Jean P Baudrillard. The results of field research can be concluded that the phenomenon of using TikTok for teenagers, namely teenagers, means that TikTok is an application as entertainment when tired of all school activities, the reason the subject uses TikTok is because TikTok is an application that has many filters, features, and trends that make it exciting even though it is only 15-30 seconds. The existence of tiktok trends in the lives of teenagers affects lifestyles such as fashion in dressing, research subjects usually choose clothes according to their tastes or trending models and also influence eating behavior that follows the type of food that is popular. TikTok trends also affect the style of language in the lives of teenagers such as using slang more often in communicating. Teenagers' free time is spent more on activities such as hanging out with friends to create TikTok content, but there are also those who spend their free time sleeping